Continuous-wave cascaded second Stokes diamond Raman laser at 1477 nm - Heinzig, Matthias; Palma-Vega, Gonzalo; Yildiz, Benjamin; Walbaum, Till; Schreiber, Thomas; Tuennermann, Andreas (Optics Letters, 2021)
We report a high brightness cascaded Stokes diamond Raman laser with a diffraction limited beam quality pumped by an Yd-doped fiber laser. The Raman laser operated at 1477 nm and reached an output power of 63 W with 214 W pump power in continuous-wave mode. Conversion efficiency over 30% was achieved using a single pump pass concentric cavity that was highly resonant at the first Stokes and had high outcoupling at the second Stokes (45%). Thermal limitations were investigated as well as the temporal behavior of the first and second Stokes intra-cavity power.
CRIS-Team Scopus Importer:2023-04-20